Current usage of inclisiran for cardiovascular diseases: overview of current clinical trials - Harbi, Maan H. (Frontiers in Pharmacology, 2025)
BackgroundCardiovascular diseases are predominant health conditions across the world due to their rising prevalence and association with several disorders. Inclisiran, a small interfering RNA (siRNA) therapy, lowers low density lipoproteins cholesterol (LDL-C) by targeting proprotein convertase subtilisin/kexin type 9 (PCSK9). Its exact role in cardiovascular diseases is not fully understood.AimThis review examines current usage of Inclisran for cardiovascular diseases.MethodA detailed search of Clinicaltrials.gov was conducted to identify relevant studies that investigated heart diseases using Inclisran. Data on study design, sample size, intervention details, and outcomes related to Inclisran were extracted and analyzed.ResultsAs of 30 December 2024, there were 92 clinical trials on involving inclisiran found at clinicaltrials.gov. The investigation focused on studies that used inclisiran for cardiovascular diseases and found that limited clinical trials were identified with limited interventional measures. The final number of analyzed trials was 11. The follow-up duration ranged from 270 to 1,695 days with a total of 214,176 participants with a favorable safety profile and twice-yearly dosing after initial loading dose. The collective findings from these trials demonstrated effective LDL-C and PCSK9 lowering compared to baseline measurements. Most studies focused on LDL-C lowering rather than measuring cardiovascular outcomes.ConclusionAlthough the studies showed inclisiran to lower LDL-C effectively, the evidence is still limited with regards to cardiovascular outcomes data. There is a need for real world studies addressing long-term safety, adherence and cost-effectiveness and therapeutic outcomes of combination therapy.